ICF-CY as a Framework for Understanding Child Engagement in Preschool - Adolfsson, Margareta; Sjöman, Madeleine; Björck-Åkesson, Eva (Frontiers in Education, 2018)
Engagement in preschool predicts children’s development, learning and wellbeing in later school years. The time children engage in activities and social interactions is conditional for pre-school inclusion. Engagement is part of the construct participation, which is determined by attendance and involvement. Two suggested underlying dimensions of engagement had been identified as essential when assessing children’s participation in preschool activities. As engagement is a key question in inclusion of all children, and preschool becomes a common context for them, it is increasingly important to understand the concept of engagement in those settings. In Sweden most children attend preschool but children in need of special support tend not to receive enough support for their everyday functioning. This study aimed to conceptualize child engagement in preschool with ICF-CY as a framework to clarify core and developmental engagement dimensions included in Child Engagement Questionnaire (CEQ). The content of CEQ was identified through linking processes based on ICF linking rules with some exceptions. Specific challenges and solutions were acknowledged. To identify engagement dimensions in the ICF-CY, CEQ items related to ICF-CY chapters were integrated in the two-dimensional model of engagement. Findings showed that engagement measured for preschool ages was mostly related to Learning and Applying knowledge belonging to Activities and Participation but the linkage detected missing areas. Broader perspectives of children’s everyday functioning requires extended assessment with consideration to mutual influences between activites, participation, body functions, and contextual factors. Related to core and developmental engagement, findings highlight the importance for preschool staff to pay attention to how children do things, not only what they do. Activities related to core engagement include basic skills; those related to developmental engagement set higher demands on the child. Linking challenges related to preschool context were not consistent with those reported for child health. Using the ICF-CY as a framework with a common language may lead to open discussions among persons around the child, clarify the different perspectives and knowledges of the persons, and facilitate decisions on how to implement support to a child in everyday life situations in preschool and at home.